ANALISIS PENERAPAN SISTEM INFORMASI AKUNTANSI PENJUALAN DI PT.EDITA PUTRA PERKASA - Permana, Ryan Syah; Mulyono, Doddy; Saragih, Guntur Syahputra (Bussman Journal : Indonesian Journal of Business and Management, 2023)
The objectives of this research are: 1) To find out sales procedures at PT. Edita Putra Perkasa. 2) To find out the implementation of the sales accounting information system at PT. Edita Putra Perkasa. This research uses a qualitative method with a qualitative descriptive approach by comparing existing theories with the reality that occurs at PT. Edita Putra Perkasa. The data collection techniques used are interview techniques, observation and documentation. Data analysis uses three types of analysis, namely: data reduction, data display, and conclusion drawing. The validity of the data uses triangulation from other sources that can be accounted for. The results of this research show that; 1) Sales procedures at PT. Edita Putra Perkasa starts from the sales department, getting and receiving orders from customers and preparing the goods to be delivered. Then the administration section receives payment from the buyer then hands over the goods to the buyer then provides proof of purchase in the form of a note/receipt and the recording section records the results of the sales transactions that have occurred. 2) Research results regarding the implementation of the sales accounting information system at PT. Edita Putra Perkasa already has a compatibility between the theory used and the reality that occurred. Where the 4 (four) components of the accounting system contained in the theory used are in accordance with the conditions that occur and there is conformity